Ancient Egyptian Concepts of Bodily Decay in the Old Kingdom Part 1, PT 684 - Eaton, Katherine (Zeitschrift für ägyptische Sprache und Altertumskunde, 2018)
Old Kingdom descriptions of bodily decay are surrounded by assertions of revivification and the maintenance of a proper offering ritual. Thus, the contexts of lines describing bodily decay are first examined, focusing on Pyramid Text (PT) Utterance 684. The problems of preventing the decay of the corpse, and curing conditions of the living body associated with decay were interrelated in ancient Egyptian thought. Already in the Old Kingdom, terminology surrounding wet, drippy decay ( r ḏ w , fdt , ḥ w Ꜣ and ḥ w ꜢꜢ .t ) was clear and well developed; sometimes incorporated into the offering ritual through association with libations; and paralleled in medical literature. In contrast, terminology which appears to refer to dry decay ( jmk , rpw ) is rare, and does not have more general uses outside of mortuary literature.